Improving The Theoretical Foundations of Using The Pirls International Assessment Program In Educational Integration - Rajabova Kimyoxon Farmonovna (Indonesian Journal Publisher, 2025)
The significance of international evaluation initiatives, specifically the PIRLS (Progress in International Reading Literacy Study) programme, in raising educational standards is examined in this article. By evaluating primary school pupils’ reading and comprehension abilities, this program – which involves more than 100 countries worldwide – assists in determining the advantages and disadvantages of national educational systems. Additionally, the article compares research conducted by local scholars, historical pedagogical heritage, and international experiences, including creative approaches in Finland’s educational system. The PIRLS programme should be seen as an opportunity to enhance education rather than as a tool for teachers and students to control one another. This strategy is essential to bringing Uzbekistan’s national education system up to date with contemporary, global norms.